MAN BEHIND THE BEARD - Dominy, G. A. (Graham Andrew), author. (ABINGDON)
1 online resource
Keywords: Deneys Schreiner was an academic, a scientist and a man of strong liberal principles, with a good sense of humor and widespread interests in the sciences, arts and public affairs. In his steady way, he transformed the University of Natal and the community around it. Between the 1960s and 1980s, Schreiner supported and initiated several endeavors to promote constitutional futures other than those imposed by the apartheid government. One of the most significant was the Buthelezi Commission, which he chaired. This biography sets out the context of the times in which Schreiner lived and his life from his ancestors to his tenure as Vice-Principal. This book is created with extensive archival research, supported by interviews with family members, former colleagues, friends, and journalists. Schreiner was a man who made a considerable contribution to the struggle for democracy in South Africa. And then there is the story of his beard, once described as a potent symbol of his presence and implacable integrity. Print edition not for sale in Sub Saharan Africa.